2021
DOI: 10.1097/md.0000000000026520
|View full text |Cite
|
Sign up to set email alerts
|

The correlation between mental health status, sleep quality, and inflammatory markers, virus negative conversion time among patients confirmed with 2019-nCoV during the COVID-19 outbreak in China

Abstract: The 2019 coronavirus disease (COVID-19) has spread to the whole world. Psychological and sleep problems among confirmed patients have drawn extensive attention which may be highly related to immune function and inflammatory responses of people. The aim of this study is to examine the correlation of mental health status, sleep quality, and inflammatory markers, virus negative conversion time (NCT) among confirmed patients during the COVID-19 outbreak. A cross-sectional survey was conducted in this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 50 publications
0
16
0
1
Order By: Relevance
“…Studies scoring ≥ 3 were regarded as low risk of bias, while studies scoring < 3 were regarded as high risk of bias (Table 2 ). The most investigated inflammatory markers were readily available routine biomarkers of inflammation, especially CRP [ 10 , 13 , 26 , 34 , 98 , 110 – 115 ] and neutrophil/lymphocyte ratio (NLR) [ 10 , 13 , 110 , 112 , 114 – 117 ]. Among cytokines, the most investigated were IL-6 [ 34 , 111 – 115 , 118 , 119 ], IL-10 [ 34 , 111 , 112 , 120 ], and TNF-α [ 111 , 112 , 118 , 120 ].…”
Section: Neurobiology Of Post-covid-19 Depressive Symptomsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies scoring ≥ 3 were regarded as low risk of bias, while studies scoring < 3 were regarded as high risk of bias (Table 2 ). The most investigated inflammatory markers were readily available routine biomarkers of inflammation, especially CRP [ 10 , 13 , 26 , 34 , 98 , 110 – 115 ] and neutrophil/lymphocyte ratio (NLR) [ 10 , 13 , 110 , 112 , 114 – 117 ]. Among cytokines, the most investigated were IL-6 [ 34 , 111 – 115 , 118 , 119 ], IL-10 [ 34 , 111 , 112 , 120 ], and TNF-α [ 111 , 112 , 118 , 120 ].…”
Section: Neurobiology Of Post-covid-19 Depressive Symptomsmentioning
confidence: 99%
“…Finally, two studies investigated T-cell subpopulations [ 111 , 120 ]. Among the included studies, 13 studies [ 10 , 13 , 26 , 34 , 98 , 111 – 113 , 115 – 117 , 119 , 120 ] found a significant association between inflammatory markers and COVID-19-related depressive symptoms, while three studies did not find any statistical association [ 110 , 114 , 118 ]. Specifically, post-COVID-19 depressive symptoms were found to be associated with NLR in four studies [ 112 , 115 – 117 ], with CRP in four studies [ 34 , 98 , 113 , 115 ], with systemic inflammation index (SII) in three studies [ 10 , 13 , 26 ], with the neutrophil count in two studies [ 115 , 117 ], and with IL-6 in two studies [ 34 , 113 ].…”
Section: Neurobiology Of Post-covid-19 Depressive Symptomsmentioning
confidence: 99%
“…Zhang et al found that poor sleep quality in infected patients was associated with increased neutrophil-to-lymphocyte ratio (NLR), lower recovery from lymphopenia, longer hospitalization, and higher risk of ICU admission [ 25 •]. Li et al exhibited that NLR was increased in patients with poor sleep quality and sleep deprivation was positively correlated with virus negative conversion time [ 26 ]. In a prospective cohort study, poor sleep quality in COVID-19 patients was significantly associated with prolonged hospitalization, major dysregulation of immune system, indicated by several biomarkers, and increased risk of developing severe or critical pneumonia [ 27 ••].…”
Section: Sleep Disorders In Covid-19 Patientsmentioning
confidence: 99%
“…Hasil analisis kajian dari penelitian yang dilakukan oleh Gennaro et al (2020); Kandeğer et al (2021); Guo et al (2020); dan; Li et al (2021) menunjukkan bahwa konsekuensi kejiwaan terhadap infeksi SARS-CoV-2 dapat disebabkan oleh respons kekebalan terhadap virus itu sendiri. Ditemukan kajian terkait respon imun dalam tubuh yang memicu peradangan atau inflamasi dasar (SII) pada status psikopatologis menemukan efek yang signifikan terhadap gangguan kesehatan mental seperti depresi dan insomnia.…”
Section: Kondisi Fisik Akibat Manifestasi Virus Covid-19unclassified